Extracellular buffer choice influences acid-base responses and gastrointestinal symptoms. Issue 6 (2nd November 2021) - Peacock, J.; Sparks, S.A.; Middlebrook, I.; Hilton, N.P.; Tinnion, D.; Leach, N.; Saunders, B.; McNaughton, L.R.
ABSTRACT: To compare the bicarbonate kinetics and gastrointestinal (GI) symptom responses between an equal dose of sodium bicarbonate and sodium citrate using delayed-release capsules. Thirteen active males (age 20.5 ± 2.1 y, height 1.8 ± 0.1 m and body mass [BM] 76.5 ± 9.6 kg) consumed either 0.3 g . kg −1 BM sodium bicarbonate, sodium citrate or a placebo, using a double-blind, randomized crossover design. Blood bicarbonate ion (HCO3 − ) concentration, pH and GI symptoms were measured pre-consumption and every 10 min for 180 min post-consumption. Blood HCO3 − concentration ( P < 0.001) and pH ( P = 0.040) were significantly higher in the sodium bicarbonate condition compared with sodium citrate condition up to 3 h post-consumption. Peak blood HCO3 – concentration was significantly higher with the sodium bicarbonate compared with citrate ( P < 0.001). Mean GI symptom scores were lower ( P = 0.037) for sodium citrate (1.5 ± 1.8 AU) than bicarbonate (2.6 ± 3.1 AU), with considerable inter-individual variability. No GI symptoms were reported following consumption of the placebo. Both substances increase HCO3 − values significantly, with sodium bicarbonate causing significantly higher pH and HCO3 − values than the same dose of sodium citrate, but results in slightly more severe GI symptoms.